Preliminary Ethnopharmacological Survey of Plants Used in Mexico for the Treatment of Hypertension - Castillo-España, Patricia; Cisneros-Estrada, Alba; Garduño-Ramírez, Ma. Luisa; Hernández-Abreu, Oswaldo; Ramírez, Rolando; Estrada-Soto, Samuel (Pharmacognosy Reviews)
Traditional Mexican medicine is one of the most important health systems in the world, among Chinese and Indian systems. Furthermore, medicinal plants play an important role in these systems. Investigation of medicinal plants allowed the isolation of several active compounds that have been used as leads for the developing of several therapeutic agents. In this context, from our continuous effort for the investigation of Mexican medicinal plants from different point of views, in this opportunity we are reporting a preliminary ethnopharmacologic, chemical and pharmacological survey of 186 plant species used in Mexico for the treatment of hypertension. From these, it was registered a total of 163 genera and 76 families and is important to mention that the most abundant were Asteraceae (17), Lamiaceae (12), Solanaceae (11), Fabaceae (10) and Rutaceae (8). Moreover, 85 were wild type. To the best of our knowledge, 47% of the total was studied at least once from phytochemical point of view and 74% were subjected to investigation of in vitro and in vivo pharmacological assays. These last investigations were carried out in order to validate their medicinal uses as antihypertensive agents in the Mexican traditional medicine.
Keywords: antihypertensive; ethnomedicinal knowledge; Mexican medicinal plants; vasorelaxant effect